Vaginismus: An Approach from biology to psychological aspect - Bintang Arroyantri Prananjaya; Syarifah Aini; Jiann Lin Loo; Diyaz Syauki Ikhsan; Puji Rizki Suryani; Alessandro Syafei Rashid (Jurnal Psikiatri Surabaya, 2023)
Background: The prevalence of vaginismus ranges from 1-6%, and the ratio becomes 5%-17% in clinical setting, although it varies widely worldwide. The main cause of vaginismus is not known, but is often considered multifactorial. This paper aims to describe the factors that contribute to vaginismus. Case: A 26 years old, married woman, health practitioner presented with the complaint of not being able to have sexual intercourse. About 1 month ago, since marriage, the patient was unable to have sexual intercourse with her husband. The patient feels guilty and anxious because of the inability to please her husband. The patient's father was very dominant and was a "religious" type of parent who always gave advice with religious aspects regarding all matters. The patient's mother was a nervous person and always said that what the father said was a law that had to be obeyed. Likewise, talk about sex is a taboo topic of discussion and is considered embarrassing. Discussion: Many factors need to be explored related vaginismus. In the case, the biological aspect can be ruled out because the patient has consulted with the ob-gyn doctor. from the psychological aspect; perceptions, attitudes and attitudes towards sex and the values ​​held by parents contribute to vaginismus in this patient. Conclusion: a therapeutic approach which focuses on all aspects promises quite good therapeutic outcomes.